Cross-linking effect on dentin bond strength and MMPs activity. Issue 2 (February 2018) - Mazzoni, Annalisa; Angeloni, Valeria; Comba, Allegra; Maravic, Tatjana; Cadenaro, Milena; Tezvergil-Mutluay, Arzu; Pashley, David H.; Tay, Franklin R.; Breschi, Lorenzo
Highlights: EDC pre-treatment efficiently preserves bond strength over time. Pre-treatment with EDC resulted in an almost complete inhibition of MMPs. Changes within the dentin matrix promoted by EDC are not adhesive-system-dependent. Abstract: Objective: The objectives of the study were to evaluate the ability of a 1-ethyl-3 (3-dimethylaminopropyl) carbodiimide (EDC)-containing primer to improve immediate bond strength of either self-etch or etch-and-rinse adhesive systems and to stabilize the adhesive interfaces over time. A further objective was to investigate the effect of EDC on the dentinal MMPs activity using zymographic analysis. Methods: Freshly extracted molars (n = 80, 20 for each group) were selected to conduct microtensile bond strength tests. The following groups were tested, immediately or after 1-year aging in artificial saliva: G1: Clearfil SE (CSE) primer applied on unetched dentin, pretreated with 0.3 M EDC water-solution for 1 min and bonded with CSE Bond; G2: as G1 but without EDC pre-treatment; G3: acid-etched (35% phosphoric-acid for 15s) dentin pretreated with 0.3 M EDC, then bonded with XP Bond (XPB); Group 4 (G4): as G3 without EDC pre-treatment. Further, gelatinase activity in dentin powder treated with CSE and XPB with and without EDC pre-treatment, was analyzed using gelatin zymography. Results: The use of 0.3 M EDC-containing conditioner did not affect the immediate bond strength of XPB or CSE adhesive systems (p > 0.05), while it improved the bond strength after 1 year of aging (p < 0.05). Pre-treatment with EDC followed by the application of CSE resulted in an incomplete MMPs inactivation, while EDC pretreatment followed by the application of XPB resulted in an almost complete inactivation of dentinal gelatinases. Significance: The μTBS and zymography results support the efficacy of EDC over time and reveal that changes within the dentin matrix promoted by EDC are not adhesive-system-dependent.